Haar wavelet collocation method for the investigation of micropolar fluid flow in a porous channel with suction and injection. (8th March 2022) - Karkera, Harinakshi; Katagi, Nagaraj N.
In this paper, the problem of micropolar fluid flow in a porous channel is analysed using a novel concept of Haar wavelet-based numerical method. Haar wavelet approach is explored for the first time for the solution of higher order coupled nonlinear boundary value problems without employing linearisation technique. The objective is to demonstrate the simplicity and efficiency of the proposed numerical scheme to find the approximate solution for the governing problem. Using suitable similarity transformations, the resulting nonlinear coupled differential equations of fourth order are solved to acquire a complete description of the micropolar fluid flow in a porous channel. Error analysis is performed to authenticate the accuracy of the results obtained. The behaviour of velocity and microrotation profiles in the flow channel driven by the influence of wall porosity are explained in detail through graphs and tables for pertinent parameters like Reynolds number Re and microrotation boundary parameter s ∈ [0, 1/2]. The new method presented in this study found to be powerful and promising to obtain solutions of different nonlinear boundary value problems.